GOVERNMENT EFFORTS TO ENHANCE PUBLIC GREEN OPEN SPACES - Ferizko, Adia (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
This research explores the government's initiatives to improve public green open spaces in Pekanbaru City. Utilizing a qualitative approach, data were obtained through interviews, field observations, and documentation. The results show that the government has implemented a range of measures, such as urban spatial planning strategies, the construction of parks and green areas, and programs to raise environmental awareness. Despite these efforts, several obstacles persist, including scarce land availability, limited public involvement, inadequate funding, weak coordination among agencies, and the lack of green spaces in densely populated areas of the city.